Effect of Potassium Chloride Supplement in Salt Blocks on the Fattening Performance of Charolais Crossbred Beef Cattle under Heat Stress - Umpapol, Hanchai; Jitrajak, Tharadol; Songvicha, Choompol; Tantisirin, Pannapa; Hanmontree, Reungrit; Sripandon, Jesda; Umpapol, Sumontip (Pakistan Journal of Nutrition, 2016)
The effect of potassium chloride (KCl) supplement in salt blocks on the fattening performance of Charolais crossbred cattle under heat stress was evaluated in the present experiment. The fattening performance of beef cattle improved due to KCl supplemention of salt blocks during heat stress conditions in Thailand. Eight crossbred beef cattle (50 to 75% Charolais crossbred cattle) were randomly assigned into two groups. They were raised under the management of small holders in Sakon Nakhon, Thailand. Group 1 was provided a salt block supplemented with KCl, while group 2 was given a salt block without KCl. After a preliminary experimental period of 2 weeks, the temperature and relative humidity in the experimental houses were recorded and blood samples were collected on day 0, 90 and 180 of the experiment to determine cortisol concentrations. Changes in general physiology (rectal temperature, pulse rates, respiration rates, heat tolerance co-efficiency, HTC and sweating rates) and hematology (hematocrit, hemoglobin, blood glucose and blood urea nitrogen and cortisol concentrations) were recorded throughout the experimental period. The temperature humidity index (THI) had a highly significant effect (p<0.01) on the general physiology of the cattle between group 1 and group 2, including the following respective differences: rectal temperature (39.39±0.02 vs., 39.45±0.03°C), pulse rate (66.59±4.50 vs., 70.31±2.74 breaths/min), respiration rate (64.34±3.52 vs., 66.04±5.76 time/sec), HTC (82.65±4.38 vs., 80.94±5.04%) and sweating rate (890.14±16.74 vs., 840 ml/m2/h). Additionally, hematology and cortisol concentrations in the blood serum of fattening beef cattle in both groups were increased (p<0.01). Cattle without KCl substitute had significantly higher values (p<0.01) for animal welfare behaviors such as rumination, panting, frequency of cattle standing up and walking for water, drinking and lying down motionless for rest or sleep at the back of the stall compared to cattle given KCl supplemented in a salt block. The fattening performance of group 1 and group 2 cattle were significantly different (p<0.05) as follows: final weight (672.20±2.80 vs., 652.62±4.48 kg), ADG (0.660±0.003 vs., 0.609±0.001 g/d), dressing percentage (61.40±0.74 vs., 57.20±0.80%) and marbling (3.74±0.02 vs., 3.74±0.02%). It is concluded that KCl-supplemented salt blocks are capable to improve fattening performance of beef cattle in semi-tropical countries.